IMPACT OF COCONUT PRODUCTION ON THE ENVIRONMENT AND THE PROBLEMS FACED BY COCONUT PRODUCERS IN LANAO DEL NORTE PROVINCE, PHILIPPINES - Ismail Bulent GURBUZ; Mike MANAROS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this study is to examine the situation of rural tourism in Azerbaijan, its impact on rural development and the rural tourism awareness levels among the students. The research was carried out with 418 students in the Agricultural Economics Department of Azerbaijan State Agricultural University in the academic year of 2018-2019. Data were analysed using SPSS 24.0 statistical software. T-test and one-way analysis of variance, Tukey test was used for the analysis of the independent samples. Research determined that there was no statistically significant difference between the age, school level and monthly total household income variables while the rural tourism awareness level of the students differed significantly according to their gender, place of residence, mother and father occupational status. Students' holiday habits were also examined in the second part and their participation in statements related to rural tourism was analysed in the third part of the research. It is concluded that Azerbaijan has rich rural tourism potential and can be an important source of income if used correctly and will increase employment opportunities. However, it has been observed that there were problems with infrastructure, transportation, promotion and financing in rural tourism and that the work of the Ministry of Tourism was insufficient. Communication and cooperation between the institutions affiliated to the Ministry were weak. Rural tourism has been accused of accelerating cultural change and environmental problems.